Newton’s Law Learning Media Based on Android - Irdam Deni; Demmy Dharma Bhakti; Muhamad Naufal Helmi (Institut Pendidikan Indonesia, 2020)
Abstract: Simulation-based educational games are designed to simulate existing problems in order to obtain the essence or knowledge that can be used to solve these problems. The rapid development of technology now affects the learning process in elementary schools and also affects learning materials and the way in which material is delivered in the process of teaching and learning activities. At the educational stage of elementary school age children, students will tend to be more interested in games that are easy to play and in which there are bright colors and animated images that attract attention. Physics is necessary for the development of development for human welfare. Thus, it is very necessary to continue the process of understanding the concepts of Physics. Didactic Physics is a vehicle in an effort to pass on knowledge about Physics. In Didactic Physics, it is described how to understand the knowledge of Physics that has been arranged in the family of Physics as we know it today. According to (Nezarat and Miangah, 2012), the speed of development of mobile technology increases and penetrates all aspects of life so that this technology plays an important role in learning different dimensions of knowledge, including learning media. Mobile learning or mobile learning provides opportunities for students to learn while they are on the bus, outside or at work doing their part-time job. In fact, they can learn every time and everywhere they are. These opinions explain that learning with the mobile learning method provides a variety of new learning for students. Students can use their gadgets to access subject matter whenever and wherever they want. kominfo.go.id (2015) which was also published on tempo.co (2015) stated that Indonesian smartphone users are growing rapidly. Keywords: Education; Physic; Newton’s Law Abstrak: Game edukasi berbasis simulasi di desain untuk mensimulasikan permasalahan yang ada sehingga diperoleh esensi atau ilmu yang dapat digunakan untuk menyelesaikan permasalahan tersebut. Perkembangan teknologi yang pesat sekarang ini berpengaruh terhadap proses pembelajaran di sekolah dasar dan berpengaruh juga pada materi pembelajaran serta cara penyampaian materi dalam proses kegiatan belajar mengajar. Pada tahap pendidikan anak usia sekolah dasar, siswa akan cenderung lebih tertarik dengan permainan yang mudah dimainkan dan di dalamnya terdapat warna-warna cerah serta gambar animasi yang menarik perhatian. Fisika diperlukan untuk perkembangan pembangunan bagi kesejahteraan manusia. Dengan demikian sangat dibutuhkan proses penerusan pemahaman konsep-konsep Fisika. Didaktik Fisika merupakan wahana dalam upaya meneruskan pengetahuan tentang Fisika. Dalam Didaktik Fisika diuraikan bagaimana cara memahami pengetahuan Fisika yang sudah tersusun dalam rumpun ilmu Fisika yang kita kenal sekarang. Menurut (Nezarat dan Miangah, 2012), kecepatan perkembangan teknologi mobile meningkat dan menembus semua aspek kehidupan sehingga teknologi ini memainkan peran penting dalam mempelajari dimensi pengetahuan yang berbeda, termasuk media pembelajaran. Belajar melalui ponsel atau mobile learning menyediakan kesempatan bagi pelajar untuk belajar ketika mereka berada di bus, di luar atau di tempat kerja melakukan pekerjaan paruh-waktu mereka. Bahkan, mereka bisa belajar setiap waktu dan di mana-mana mereka berada. Pendapat-pendapat tersebut menjelaskan bahwa belajar dengan metode mobile learning memberikan variasi pemebalajaran baru pada siswa. Siswa dapat memanfaatkan gadgetnya untuk mengakses materi pelajaran kapanpun dan dimanapun mereka inginkan. kominfo.go.id (2015) yang juga dimuat pada tempo.co (2015) menyatakan bahwa pengguna smartphone Indonesia bertumbuh dengan pesat. Kata kunci: Edukasi; Fisika; Hukum Newton